Existence and linear conditioning for solutions of equilibrium problems in metric spaces - Le, Thi Nhu Bich; Nguyen, Thi Thu; Nguyen, Thai An (Hue University Journal of Science: Natural Science, 2025)
In this paper, we provide sufficient conditions for the existence and linear conditioning of equilibrium problems in metric spaces. Our results improve and generalise some well-known results in the literature.